ANALISIS KEBUTUHAN DAN PENGEMBANGAN TENAGA DOKTER UMUM DI PUSKESMAS NGALIYAN KOTA SEMARANG - Nurul Maulidiyah; Intan Zainafree (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Ngaliyan Public Health Center has a high number of visitos which increases every year, but inversely proportional of the number of doctors, amounting to 3 people with 1 doctor concurrently serving as the head of the Public Health Center. This causes doctors to have a high workload which has an impact on non-optimal work result. The purpose of the study is to determine the optimal number of needs and development of doctors at the Ngaliyan Public Health Center. The type of research is descriptive qualitative using quantitative data with the WISN and Miles Huberman method. Data collection method using in-depth interviews. The results of the analysis of the need for personnel indicate that the need for general practitioners based on the WISN method is 4 doctors. The results of the development analysis show that general practitioners need further formal education, training such as emergency training, disease updates, primary healthcare center management training, mutations that are carried out regularly and the opportunity to obtain a higher position than the previous position. Suggestions in this study are to add doctors as needed, conduct surveys to general practitioners to find out the development needed and support the development of general practitioners by providing development programs through education, training, transfers and promotions.